CODE SWITCHING ON A CHICKLIT NOVEL: Beauty Case by Icha Rahmanti - Novika Hani Fauzia, - (2008)
Phis paper. entitled Code Switching on a Chicklit Novel: Beauty Case by Icha Rahmanti. examines the realization of code switching in the novel. This paper elaborates two maJ01' problems. First, it investigates the types of code switching that occurred. Second. it examines the functions of code switching that occurred in the novel the present studv is a studv and is largely qualitative. Some quantification is also used to support the qualitative procedure. The data were taken trom the novel. [he writer highlighted 250 code switching. There are several stages in analvzing the data- namely. underlining every word. phrase. and clause in the novel that contam code switching categorizing the data into a table form based on its functions and type of code switching: calculating the percentages of the occurrences of each type and functions: interpreting the data: and the last is drawing conclusion from the data The result of the study reveals that there are three types of code switching used by the author of the novel, namelv tag. intrasentential, and intersentential switchings. These findings 'Jive support to the previous research on code switching. The writer finds that tag switching is the most frequent and intersentential appeared least. Furthernlore. in terms of the function of code switching, there are 14 functions were identified in the data. These are personalization, reiteration. designation. substitution, emphasis. clarification. objectification. untranslatabilitv, mitigating rnessage. intenections. parenthesis- aggravating message. quotation. and topic shift. The function that appeared the most is topic shift. From the fact mentioned above it can be said that the author of the novel is competent in English.